DIKSI DAN GAYA BAHASA SYAIR LAGU KARYA DIDI KEMPOT - Rosmini, Rosmini; Zulianto, Sugit; Harisah, Sitti (BAHASANTODEA, 2017)
This research aims to describe the use of diction and language style of the song lyric by Didi Kempot. Sources of data obtained from the album Best Campursari, success album Vol.3, and Romantic Javanese. The study, which used in this research, is the overview of Ethnography. The method used was descriptive qualitative method. The data collection is done by two techniques: (1) listen and (2) record. The object of research was the song lyric by Didi Kempot. A data analysis technique in this research was an interactive model. The analysis of the research included four phases, namely: (1) data collection, (2) data reduction, (3) presentation of data, and (4) verification / conclusion. The results showed that the use of diction denotative and connotative that used in song lyric by Didi Kempot more often use denotative meaning, concrete and abstract words used in song lyric by Didi Kempot more often use the word concrete. The results of the study language was contained in a song lyric by Didi Kempot of â€œ Parangtritisâ€ three kinds of language styles, namely: the personification, redundancy, and assonance, song lyric of â€œ Layang Kangenâ€œ: hyperbole, assonance, and anaphora, song lyric of â€œCidroâ€: hyperbole, litotes, metaphors, personification, and euphemism, song lyric of â€œSewu Kutoâ€œ: hyperbole, sinekdoke, euphemisms and anaphora, song lyric of â€œ Janji Palsu â€œ: the personification, euphemism, assonance, and anaphora, and song lyric of â€œ Ketaman Asmaraâ€: hyperbole and personification. Cultural values contained in the lyrics "Parangtritis": religious and ethical values, lyrics "Stasiun Balapan": religious values, lyrics â€œLayang Kangen â€œ: religious values, ethical, and aesthetic, lyrics â€œCidroâ€œ: religious values, lyrics â€œSewu Kutoâ€œ: religious values and aesthetic, lyrics of â€œJanji Palsuâ€: religious values, and lyrics of â€œKetaman Asmaraâ€: ethical and aesthetic values.Â